Endovascular Management of a Rare Cause of Bleeding Per Vaginam: A Hole in the Mole - Chahal, Anurag; Malla, Sundeep; Gamanagatti, Shivanand (Journal of Clinical Interventional Radiology ISVIR, 2019)
Uterine artery aneurysm is a rare cause of bleeding per vaginam. Uterine artery pseudoaneurysms are rare but potentially life-threatening causes of persistent or delayed bleeding post-uterine curettage or any uterine surgery. Color Doppler ultrasonography is very useful for emergent diagnosis of these conditions and subsequent follow-up post-embolization. Computed tomography scan and magnetic resonance imaging play an important role in confirming the diagnosis. Transcatheter arterial embolization is the therapy of choice for such cases. Our case highlights the presentation, imaging appearance, and endovascular management of a case of uterine artery pseudoaneurysm.
Keywords: uterine artery; pseudoaneurysm; embolization